Direct synthesis of well-ordered mesoporous Al-SBA-15 and its correlation with the catalytic activity - Bhange, Pallavi; Bhange, Deu S.; Pradhan, Sivaram; Ramaswamy, Veda (Applied Catalysis A-General, 2011)
The synthesis of Al-SBA-15 under milder acidic conditions were made through an adjusting the molar H(2)O/HCl ratio which indicate the formation of Si-O-Al linkages that lead to isomorphous substitution of Si(4+) by some Al(3+) ions. By adjusting the H(2)O/HCl molar ratio, Al gets incorporated into the lattice of SBA-15, which is evidenced by XRD. N(2) adsorption, TEM, (29)Si and (27)Al MAS NMR spectroscopic data. Aluminium incorporated SBA-15 samples retained both structural and textural properties of SBA-15. The (27)Al MAS NMR confirms that a large proportion of the Al is inserted into tetrahedral positions within the framework. The Al(3+) ions could assume a tetrahedral coordination and be part of the hexagonal structure of silica in Al-SBA-15. In the present study, we have examined the effectiveness of Al-SBA-15, as an acid catalyst for the esterification of acetic acid and in benzylation of anisole. The high activity of Al-20 sample in esterification reaction has been attributed to isolated, generally tetrahedrally coordinated, framework Al species. While in benzylation of anisole, the best result was achieved with Al-5 catalyst. The selectivity for benzylanisole increases and that for dibenzylether decreases with increase in the Si/Al ratio of Al-SBA-15. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Al-SBA-15; Benzylation of anisole; Esterification of acetic acid

Immobilization of bile salt hydrolase enzyme on mesoporous SBA-15 for co-precipitation of cholesterol - Bhange, Pallavi; Sridevi, N.; Bhange, Deu S.; Prabhune, Asmita; Ramaswamy, Veda (International Journal of Biological Macromolecules, 2014)
We describe herein a simple and effective strategy for immobilization of bile salt hydrolase enzyme by grafting glutaraldehyde groups inside channels of APTES functionalized SBA-15. The increase in glutaraldehyde concentration prevents leakage of enzyme but showed a steep decrease in enzyme activity in the immobilized matrix. So the degree of cross-linking should be the minimum possible to ensure sufficient stability without loss of activity. Cross-linking carried out with 0.1% glutaraldehyde concentration showed the highest activity, so this was used in all further experiments. Physico-chemical characterizations of the immobilized enzyme were carried out by XRD, N-2 adsorption, TEM, FUR and Si-29 CP-MAS NMR techniques. Immobilized BSH exhibits enhanced stability over a wide pH (3-11) and temperature range (40-80 degrees C) and retains an activity even after recycling experiments and six months of storage. From our in vivo research experiment toward co-precipitation of cholesterol, we have shown that immobilized BSH enzyme may be the promising catalyst for the reduction of serum cholesterol levels in our preliminary investigation. Enhancement in pH stability at the extreme side of pH may favor the use of immobilized BSH enzyme for drug delivery purpose to with stand extreme pH conditions in the gastrointestinal conditions. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bile salt hydrolase; Co-precipitation of cholesterol; SBA-15